A utilização da grafologia nos processos de seleção de pessoal - Faissal, Reinaldo (2002)
This research has the objective of analyze the possibilities offered by the use of the graphology in the process of personnel's selection that aim at the completion of current vacancies of job offers. The study is based in the verification of the applicability and forms of use of selection instruments of personal, mainly of those developed with objective of identifying the aptitudes and the characteristics of the individual's personality. Analyzing its applicability, as form of adapting to the reality today, the graphology, besides assisting to the new variables that the global changes impose to the individuals' behavior and his relationship with the companies, appears as alternative and it is occupying, every day, more space in the professional evaluation area. This study offers reasons so that one can consider the graphology analysis as one more instrument to be used in personnel's selection, in agreement with the possibilities and identified limitations, when used for that end. Tends as objective to explain the reasons of the use of the graphology analysis as evaluation tool, the exploratory and explanatory researches were adopted. This explanation will appear, then, of the verification and analysis of the data obtained in the bibliographical and of field researches, which allows like this to base its report, development and applicability.